Underwater Optical Wireless Communications With InGaN LEDs Grown With an Asymmetric Multiple Quantum Well for Light Emission or Detection - Chia-Lung Tsai (IEEE, 2022)
InGaN light-emitting diodes (LEDs) grown with an asymmetric multiple quantum well (MQW) are proposed for use in an optical link with an avalanche photodiode (APD) based receiver. In contrast to the high photoresponse of red AlGaInP LEDs in APDs, the proposed blue LEDs provide improved light output and enhanced system bandwidth for directed line-of-sight optical links passing through a 100-cm-long water tank. This improvement is due to the nonuniform carrier distribution within the InGaN MQWs being mitigated by using a thin GaN barrier near the n-GaN to facilitate hole transport capacity. In addition, bandwidth degradation resulting from APD module saturation can also be avoided by using these blue LEDs, successfully establishing a 300 Mbit/s LED-based underwater data link. The proposed InGaN LEDs (zero bias) under illumination exhibit a peak responsivity of 0.133 at λ = 370 nm, an ultraviolet (UV)-to-visible rejection ratio of 4849 and a 3-dB cut-off frequency of 33.3 MHz. Using violet UV laser diodes and the proposed LEDs respectively as the optical transmitter and receiver, an underwater optical link (L = 100 cm) with a data transmission rate of up to 130 Mbit/s and a bit error rate of 4.2 × 10−9 is also demonstrated.